Survey on Clinical Incidence of Dermatophilosis in Cattle in Southern Plateau State - Gofwan P. G.; Abdullahi U. S. (Nigerian Journal of Animal Science and Technology (NJAST), 2019)
A study was conducted to determine the incidence of clinical dermatophilosis in cattle in Southern Plateau State, Nigeria. Five (5) out of six (6) local government areas (LGA) were randomly selected and 5044 cattle were examined. Skin scrapping from suspected dermatophilosis lesions was collected from 215 cattle. The samples were processed and cultured on blood agar medium at 370 C for 48-72 hours under microaerophilic condition. Small golden yellow colonies that pitted on the media were considered dermatophilosis positive. The isolates were further examined biochemically to confirm those positive for dermatophilosis. The results showed that from the 215(4.26%) samples, 196 (3.89%) were positive with high percentage from Shendam LGA with 51 cattle (26.02%). In regard to sex 140 (71.43%) females of the 196 were positive and 56 27.57%) males were positive. The adults had more positive of 184 (93.88%) against 12 (6.12%) young. the cattle with white colours had more positive of 175 (89.29%) while other colours spotted, red and black had few that were positive 10, 7and 4 or5.10%, 3.57% and 2.04% respectively . Results from the lesion distribution indicated that chest had high number (35 or 17.88%) of the 196 with positive lesions while leg had the least number (27 or 13.78%) with positive lesions. In conclusion, dertmatophilosis exist in Southern Plateau State but the incidence was low. Therefore, preventive measures to eradicate the disease are suggested.